If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1c = -14 Solving 9 + -1c = -14 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1c = -14 + -9 Combine like terms: 9 + -9 = 0 0 + -1c = -14 + -9 -1c = -14 + -9 Combine like terms: -14 + -9 = -23 -1c = -23 Divide each side by '-1'. c = 23 Simplifying c = 23
| 5n+-50=55 | | 7x-9y=19fory | | 6a^2-4a=2a | | 14=15x-(2x+12) | | 9x+5x+2+6=10x+4+3x | | 1(5x+8)2=375 | | 9(x-3)+6(x-1)=2x | | abs(7x-4)=abs(4x-8) | | x^3+8x-4=0 | | a^2*x^3-1/8*a^2*(1+x)^3 | | 0.5+7y=-25 | | 4(x-1)-(5-2x)=5 | | 6(x-3)+1=10 | | 2(X-10)=70 | | C=A(150c) | | 3(5x+8)=375 | | a^2x^3-1/8a^2*(1+x)^3 | | x^3+8x+2=0 | | 9(w+3)=5w-13 | | y=1.23x+0.19x^2 | | 6x=4(5-x) | | 7(1-4b)=231 | | 7x^2+2sqrt(14)x+2=0 | | 4x+5x-9=2 | | 7-8(-6+8k)=119 | | 2x(3x-1)=5x+1 | | -5(5-8r)+4r=-113 | | 15x-2x+7=9+15-4x | | 4(x-3)=7 | | -3(4-4a)+a=92 | | 5x^2-5x=14 | | 4(-6+8v)=-120 |